Glandular amputation by strangulating tied suture: a case report of late-onset complication in the Plastibell circumcision technique - Jalil Hosseini; Saeid Haghdani; Nima Narimani (BMC, 2019)
Abstract Background Circumcision is considered to be a procedure with minimal morbidity but may be associated with catastrophic complications in inexpert hands. Case presentation We presented a 9-year-old boy with a past medical history of circumcision at the age of one year with Plastibell clamp who was referred with severe chronic penile injury due to neglected plastibell string. After string removal under a loupe magnification (4×), we saw a deep circular injury at distal penile shaft which led to painless glandular autoamputation 45 days later. The patient was managed conservatively with daily urethral self-dilation until future reconstructive surgery. Conclusion This complication emphasized the importance of the follow-up visit by a physician for any probable string remnant.